Mesa redonda: ¿Los animales pueden ser considerados sujetos de derecho? Un análisis sobre la Ley de Protección y Bienestar Animal y la última sentencia del Tribunal Constitucional que declara constitucional sus excepciones - Franciskovic Ingunza, Beatriz (2020)
The current round table gathers three renowned specialists: Beatriz Franciskovic, from the perspective of Constitutional Law; Enrique Varsi, from the perspective of Civil law; and Pierre Foy Valencia, from the perspective of Animal Law, in order to analyze the current state of animals in the legal system, considering the Law 30407 – Ley de Protección y Bienestar Animal, and the last judgment of the Constitutional Court about bullfights and cockfights. Thus, the guests address the implication of considering animals as a subject of law, and the limitation of legal system to establish and the adequate and effective regime in favor of animals.